Balancing infrastructure, ecosystem conservation, and community approaches on integrated development planning of Citarum Watershed - Andi Setyo Pambudi (Indonesian Journal of Applied Environmental Studies, 2022)
The condition of several watersheds in Indonesia at this time has experienced a lot of decline in functions in maintaining water availability and environmental health. The number of critical watersheds in Indonesia continues to grow and is getting worse even though there have been many rehabilitation programmes for several watersheds in Indonesia, including the Citarum Watershed in West Java. Changes in the characteristics of the Citarum Watershed that can be seen include an increase in the overflow point of flood inundation, erosion of agricultural land, and sedimentation in rivers. The method used in this research is a qualitative approach through analysis based on a literature review of planning documents, regulations, books, journals, and expert judgment analysis. This study aims to assess the extent to which cross-sectoral, cross-regional and inter-disciplinary problems affect regional development and analyze problems that occur at the watershed scale. The Citarum Watershed Strategic Plan is a set of activities with steps to implement the planned strategies. The Strategic Plan reveals some activities, involvement of stakeholders, and also goals for the future which are to be achieved through the identified implementation steps. All of the activities have a main vision: "All stakeholders working together to enhance the quality of watershed carrying capacity by balancing infrastructure, ecosystem conservation, and community approaches".